POLA PAMOR KERIS TANGGUH SURAKARTA - Sulistyo Djoko Suryono (Institut Seni Indonesia Surakarta, 2004)
Keris in past represent weapon grasp expanding trought in the Nusantara, Philipina, Malayan, and also in south-east Asia. Keris in lack is not used for just weapon but expand usable as media have masterpiece at branch of artistry of masterpiece for balade smith. Others some group socialize keris assumed to have magig, or earn to generate miracle. Each other interfere in about point of view, and also bilief in keris in society there is still till this time. For that need performed a study in order get a real point of view of keris progressively.In fact keris is an object which is unobvious and is not taboo if studied exhaustively at existing pamor patterns. Pamor pattern during the time still contain mystery, inviting various interpretation until now this. Various norm and existing confidence, tried to be traced exhaustively. In Socuety there is in a view which pamour pattern have a magig, in the other hand there is also a view in which pamor pattern represent expression of the maker. Study to assessment to this pamor pattern expected will open way of assessment to patterns of pamor of keris Tangguh Surakarta. hoopfully it will create a corret way of assessment to the pamor patterns at kerisPamour pattern which traditionally happened since making systems of forged will be studied it is expected to elaborate problem and make clear in real meaning of pamor pattern. Tracing of Pamor pattern will not get out of its hitorycally background, and also scope of where that keris expand in society. Evaluation of raw material as elementary element from making keris, and also to usefulness become militant will represent a consideration about how made the hardness kerisOf vital importance for studying of pattern pamor keris tangguh Surakarta, will concerning about technique of scheme of making of pamour pattern. How is pattern earn made, and also review of raw materialand also the nature of from the substance With this study will get knowledge to constitute various means of somebody to look into to existence of pamour pattern so that earn made as stepping when going to determine value of exist in pattern of pamor keris.Keyword : Keris, Pamor, Tempa